College EFL students’ perception toward AI assistance in academic writing assignments - Agustin, Navila Zamzam; Cahyono, Bambang Yudi; Agustina, Febrina Rizky (ELT Forum: Journal of English Language Teaching, 2025)
The rapid development of Artificial Intelligence (AI) has influenced many sectors, including education, which raises a question about how students interact with AI tools. This study explored the English as a Foreign Language (EFL) college students’ perspectives on AI-assisted tools in academic writing assignments. Implementing a mixed-method approach, this study examined 76 students’ awareness of the benefits of AI and their preference for the types of AI which can assist them in academic writing assignments. The quantitative data were derived through a Likert-scale questionnaire, while the qualitative data were derived through open-ended responses. The findings revealed that most students have perceived positive benefits from AI-assisted writing. The study also highlights ChatGPT, Gemini, and Perplexity as the most preferred AI tools for accessibility and accuracy in assisting the students with their assignments. However, the findings of this study show that while the students perceive AI positively, its use also raises concerns about overreliance and academic integrity. Therefore, it is recommended that future researchers address the negative potential of AI.